Experimental Study on a New Type of Separator for Gas Liquid Separation - Zheng, Chunfeng; Yang, Wanyou; Wang, Gang; Fan, Guangming; Yan, Changqi; Zeng, Xiaobo; Liu, Antai (Frontiers in Energy Research, 2019)
Gas-liquid separation technology is widely used in various fields of industrial production. In this research, a new kind of gas-liquid separator was proposed for the separation of gas-liquid mixture under different flow patterns. An inclined experimental system with an angle of 60 degrees from the vertical was established to test the new designed gas-liquid separator using of water and air as the working fluid. The experiment was conducted with the water flow rates covering 2.85–4.17 m3/h and the gas volume fraction covering 5–90%. Experiment results show that the separator can enable high efficient separation of gas-liquid mixtures under different patterns, especially under unstable flow patterns. The liquid level inside the separator is an important factor affecting the performance of the separator. On the basis of this, the critical liquid level of the separator was proposed for the practical application of the separator. This study fills the gap in the field of gas-liquid separation and provides a method for the separation of gas-liquid mixtures under different flow patterns.